Development of lateral flow assays to detect host proteins in cattle for improved diagnosis of bovine tuberculosis - Khalid, Hamza; Pierneef, Louise; van Hooij, Anouk; Zhou, Zijie; de Jong, Danielle; Tjon Kon Fat, Elisa; Connelley, Timothy K.; Hope, Jayne C.; Corstjens, Paul L. A. M.; Geluk, Annemieke (Frontiers in Veterinary Science, 2023)
Bovine tuberculosis (bTB) caused by Mycobacterium bovis (M. bovis) infection in cattle is an economically devastating, chronic disease for livestock worldwide. Efficient disease control measures rely on early and accurate diagnosis using the tuberculin skin test (TST) and interferon gamma release assays (IGRAs), followed by culling of positive animals. Compromised performance of TST and IGRA, due to BCG vaccination or co-infections with non-tuberculous mycobacteria (NTM), urges for improved diagnostics. Lateral flow assays (LFAs) utilizing luminescent up-converting reporter particles (UCP) for quantitative measurement of host biomarkers, present an accurate but less equipment- and labor demanding diagnostic test platform. UCP-LFAs have proven application for human infectious diseases. Here, we report the development of UCP-LFAs for detection of six bovine proteins (IFN-γ, IL-2, IL-6, CCL4, CXCL9 and CXCL10) which by ELISA have been described as potential biomarkers to discriminate M. bovis infected from naïve and BCG vaccinated cattle. We show that in line with the ELISA data, the combined, PPDb-induced levels of IFN-γ, IL-2, IL-6, CCL4 and CXCL9 determined by UCP-LFAs, can discriminate M. bovis challenged animals from naïve (AUC range: 0.87-1.00) and BCG vaccinated animals (AUC range 0.97-1.00) in this cohort. These initial findings can be used to develop a robust and user-friendly multi-biomarker test (MBT) for bTB diagnosis.